2016
DOI: 10.1111/andr.12117
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of melatonin synthesis in the ram reproductive tract

Abstract: SUMMARYMelatonin is a ubiquitous molecule found in a wide range of fluids, one of them being ram seminal plasma, in which it can reach higher concentrations than those found in blood, suggesting an extrapineal secretion by the reproductive tract. In order to identify the source of the melatonin found in ram seminal plasma, we first tried to determine whether the melatonin levels were maintained during the day. For this purpose, melatonin concentrations were measured in seminal plasma obtained from first ejacul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 57 publications
4
46
0
3
Order By: Relevance
“…In the female, granulosa cells surrounding the oocyte can synthesize melatonin [42], and the melatonin receptors have been found in the ovary [43], uterus [13,44], and mammary gland [14]. In the male, melatonin is secreted in the testes [34,45], and although there are several reports of the presence of melatonin receptors MT 1 and/or MT 2 in various organs of the male reproductive tract, such as the testes [16,17], epididymis [18], or prostate [19], to the best of our knowledge this is the first time that the presence of melatonin receptors MT 1 and MT 2 have been studied in the whole male reproductive tract of one species, the sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the female, granulosa cells surrounding the oocyte can synthesize melatonin [42], and the melatonin receptors have been found in the ovary [43], uterus [13,44], and mammary gland [14]. In the male, melatonin is secreted in the testes [34,45], and although there are several reports of the presence of melatonin receptors MT 1 and/or MT 2 in various organs of the male reproductive tract, such as the testes [16,17], epididymis [18], or prostate [19], to the best of our knowledge this is the first time that the presence of melatonin receptors MT 1 and MT 2 have been studied in the whole male reproductive tract of one species, the sheep.…”
Section: Discussionmentioning
confidence: 99%
“…We have also measured seasonal variations of the melatonin concentration in ram seminal plasma [33], and we have recently demonstrated that the melatonin synthesizing enzymes are expressed in the ram testes [34], mainly in the Leydig cells, spermatocytes and spermatids. The testicular melatonin could protect the developing spermatozoa from oxidative damage [35], one of the possible mechanisms of action being through melatonin receptors in the cells [36].…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, se ha reportado la importancia de variables como la viabilidad y la velocidad curvilínea (VCL) como predictores de la fertilidad en ovinos (21), relacionado con las tres subpoblaciones espermáticas descritas para esta especie, según el patrón de cinemática que presentan (lenta, no lineal; rápida, lineal; rápida, no lineal) (28). También se ha comprobado que los espermatozoides de ovinos con alta fertilidad presentan mayores valores de viabilidad, VCL y VSL que los de ovinos de baja fertilidad (29).…”
Section: Discussionunclassified
“…El eyaculado mamífero es muy heterogéneo y contiene subpoblaciones espermáticas con importantes diferencias en sus características cinemáticas (30), o en procesos como apoptóticos, capacitados y reaccionados (acrosoma), procesos que involucran cambios en la membrana plasmática (28). Tales condiciones pueden explicar la presencia de diferentes patrones de motilidad (cinemática) que caracterizan a las subpoblaciones espermáticas, y cambios en la proporción de estas poblaciones pueden afectar el éxito en el proceso de fertilización como se ha descrito en ovinos (4), en venado rojo ibérico (31), humano (32), entre otras especies.…”
Section: Discussionunclassified
“…Melatonin (MT) ( N -acetyl-5-methoxytryptamine) is an important molecule secreted mainly by the pineal gland as well as immune cells and the digestive and reproductive systems [14,15,16,17,18]. This molecule exhibits pleiotropic physiological functions.…”
Section: Introductionmentioning
confidence: 99%